Characterization and Biodegradability of Rice Husk-Filled Polymer Composites - Yap, Saw Yin (Polymers (Basel), 2020)
The fabrication of affordable biodegradable plastics remains a challenging issue for both the scientific community and industries as mechanical properties and biodegradability improve at the expense of the high cost of the material. Hence, the present work deals with fabrication and characterization of biodegradable polymer with 40% rice husk waste filler and 60% polymer-containing mixture of polybutylene succinate (PBS) and poly butylenes adipate-Co-terephthalate (PBAT) to achieve good mechanical properties, 92% biodegradation in six months, and competitive pricing. The challenge in incorporating high amounts of hydrophilic nature filler material into hydrophobic PBS/PBAT was addressed by adding plasticizers such as glycerol and calcium stearate. The compatibilizers such as maleic anhydride (MA) and dicumyl peroxide (DCP) was used to improve the miscibility between hydrophobic PBS/PBAT and hydrophilic filler material. The component with the formulation of 24:36:40 (PBS/PBAT/TPRH) possessed the tensile strength of 14.27 MPa, modulus of 200.43 MPa, and elongation at break of 12.99%, which was suitable for the production of molded products such as a tray, lunch box, and straw. The obtained composite polymer achieved 92% mass loss after six months of soil burial test confirming its biodegradability.